Polyfunkční dům - Rzymanová, Beata (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce zpracovává projektovou dokumentaci novostavby polyfunkčního domu. Objekt je samostatně stojící. Je třípodlažní s obytným podkrovím a podsklepený. V objektu se nachází 12 bytů, 2 ordinace a 6 garáží. Ordinace jsou umístěny v přízemí objektu. Dům je postaven ze systému Heluz a zateplen kontaktním zateplovacím systémem ETICS. Střecha je křížová.

The Master’s thesis deals a project documentation of a new multifunctional building. The building is a detached. It is the three-storeyed build with attic and cellared. There are 12 flats, 2 surgeries and 6 garages. The surgeries are in the ground floor. The building is built from a Heluz system and walls are isolated by a contact thermal insulation system ETICS. Roof is a cross roof.
Multifunctional building
Keywords: Novostavba; polyfunkční dům; zdivo heluz; křížová střecha; systém ETICS; ordinace; garáž; byt; New building; multifunctional building; masonry Heluz; cross roof; system ETICS; surgery; garage; flat